2021
DOI: 10.3390/jcm10091914
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of the Fujifilm SILVAMP TB-LAM in Children with Presumptive Tuberculosis

Abstract: Current diagnostics for tuberculosis (TB) only manage to confirm a small proportion of children with TB and require respiratory samples, which are difficult to obtain. There is a need for non-invasive biomarker-based tests as an alternative to sputum testing. Fujifilm SILVAMP TB lipoarabinomannan (FujiLAM), a lateral-flow test to detect lipoarabinomannan in urine, is a novel non-sputum-based point-of-care diagnostic reported to have increased sensitivity for the diagnosis of TB among human immunodeficiency vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…However, the sensitivity of FujiLAM in HIV-infected children was approximately 55–60% and therefore lower than in HIV-infected adults [ 9 , 16 ]. Interestingly, the sensitivity in HIV-uninfected children was higher than expected, with 60–65%, and was therefore similar to that reported in HIV-infected adults [ 16 , 17 ]. The reasons behind these observations are speculative, but Mtb bacterial load and TB severity may influence the detection of LAM in urine [ 11 , 18 ].…”
Section: Currently Available Point-of-care Tests (Poct) For Childhood...supporting
confidence: 87%
See 1 more Smart Citation
“…However, the sensitivity of FujiLAM in HIV-infected children was approximately 55–60% and therefore lower than in HIV-infected adults [ 9 , 16 ]. Interestingly, the sensitivity in HIV-uninfected children was higher than expected, with 60–65%, and was therefore similar to that reported in HIV-infected adults [ 16 , 17 ]. The reasons behind these observations are speculative, but Mtb bacterial load and TB severity may influence the detection of LAM in urine [ 11 , 18 ].…”
Section: Currently Available Point-of-care Tests (Poct) For Childhood...supporting
confidence: 87%
“…The reasons behind these observations are speculative, but Mtb bacterial load and TB severity may influence the detection of LAM in urine [ 11 , 18 ]. In children specifically, FujiLAM sensitivity increased with more advanced stages of the disease, and the number of positive cases was proportionally higher among underweight and stunted children [ 17 ]. This suggests that undernutrition may facilitate bacteremia, increasing the amount of LAM in urine samples and thus the sensitivity of LAM tests [ 19 , 20 ].…”
Section: Currently Available Point-of-care Tests (Poct) For Childhood...mentioning
confidence: 99%
“…Two studies were excluded based on review of their titles and abstracts, and one study was excluded after a full-text review. Eleven studies met the inclusion criteria, and were included in this systematic review and meta-analysis ( Blok et al., 2014 ; Nicol et al., 2014 , 2021 ; Kroidl et al., 2015 ; LaCourse et al., 2018 ; Gautam et al., 2019 ; Nkereuwem et al., 2020 ; Comella-Del-Barrio et al., 2021 ; Dulce-Vasco et al., 2021 ; Schramm et al., 2021 ; Orikiriza et al., 2021 ) ( Figure 1 ). All included studies had high-quality assessment scores based on the JBI assessment checklist for diagnostic test accuracy (Table S3, see online supplementary material).…”
Section: Resultsmentioning
confidence: 99%
“…After full-text screening of the remaining studies, five were excluded because they were reviews, two were excluded because they did not evaluate the diagnostic value of FujiLAM, and one article was excluded because there were potentially repeat data (Figure 1). Finally, a total of nine articles that described the value of FujiLAM in the diagnosis of TB patients were identified (11)(12)(13)(14)(17)(18)(19)(20)(21)). Among them, three studies reported the diagnostic value of FujiLAM in pediatric patients with TB, while the rest were the diagnostic value of FujiLAM in adult patients with TB.…”
Section: General Characteristicsmentioning
confidence: 99%